Mercaptopurine induced myelosuppression in a child with a NUDT15 rs116855232 homozygous variant. (June 2023) - Gupta, Navya; Magatha, Latha Sneha; Jayaraman, Dhaarani; Scott, Julius Xavier; Antony, Sharon Benita; Koshy, Teena
Introduction: Mercaptopurine (6-MP) is the backbone of the consolidation and maintenance therapy for paediatric acute lymphoblastic leukaemia (ALL). Nevertheless, it can cause critical myelosuppression. Predicting adverse reactions to 6-MP often involves the investigation of pharmacogenetic variants; in particular thiopurine S-methyltransferase ( TPMT ) and nudix hydrolase 15 ( NUDT15 ). Lately, NUDT15 variants have been shown to play a significant pharmacogenetic role in predicting 6-MP intolerance in children of Asian descent. Case Report: We present a six-year-old male child of Indian origin with persistent cytopenia after treatment. This prompted targeted sequencing of the genes TPMT and NUD15. The results revealed two copies of the variant of NUD15 rs116855232, that is, NUDT15 *2 genotype. Management and Outcome: Since the NUDT15 *2 allele classified the patient as a poor metabolizer, he was restarted on a low dose of 6-MP, which he tolerated. Discussion: Individuals with the NUDT15 *2allele (*2/*2 genotype) are poor metabolizers of thiopurines which results in an adverse reaction to 6-MP. About 3.5% of Indians show variations in the TPMT gene as compared to 19.4% variations observed in NUDT15, which makes the latter a more reliable disease marker.